(untitled) (Circe de clásicos y modernos, 2018)
Among the medieval descriptions or Rome, known as Mirabilia, the Narracio de Mirabilibus Urbis Romae by Master Gregorious outstands because it shows the transition between the medieval vision, determined by the imcomprehension of the building’s functions and the attribution of a magical power to many of them, and the Renaissance vision, determined by the admiration of the Antiquity as cultural guide. The reading of some paragraphs, representatives of both visions, allow us to relate the reading’s possibilities of the work with the different perceptions that the ruins of Rome had generated along the history.